2019
DOI: 10.1038/s41534-019-0197-0
|View full text |Cite
|
Sign up to set email alerts
|

Squeezing-enhanced Raman spectroscopy

Abstract: The sensitivity of classical Raman spectroscopy methods, such as coherent anti-stokes Raman spectroscopy (CARS) or stimulated Raman spectroscopy (SRS), is ultimately limited by shot-noise from the stimulating fields. We present the complete theoretical analysis of a squeezing-enhanced version of Raman spectroscopy that overcomes the shot-noise limit of sensitivity with enhancement of the Raman signal and inherent background suppression, while remaining fully compatible with standard Raman spectroscopy methods.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 53 publications
(57 reference statements)
0
11
0
Order By: Relevance
“…Metrology, which studies the precision limit of measurement and estimation, plays a central role in science and technology. Recently quantum metrology, which exploits quantum mechanical effects to achieve far better precision than classical schemes , has gained increasing attention and has found wide applications in various fields, such as gravitational wavedetection [19,[23][24][25][26][27], quantum phase estimation [5,[28][29][30][31], quantum magnetometer [32,33], quantum ranging [34][35][36], quantum spectroscopy [37][38][39][40], quantum imaging [41][42][43][44][45][46][47], quantum target-detection [48,49], quantum gyroscope [50,51], distributed quantum sensing [52][53][54], atomic clocksynchronization [55][56][57][58][59][60][61], and even biological measurements [62].…”
Section: Introductionmentioning
confidence: 99%
“…Metrology, which studies the precision limit of measurement and estimation, plays a central role in science and technology. Recently quantum metrology, which exploits quantum mechanical effects to achieve far better precision than classical schemes , has gained increasing attention and has found wide applications in various fields, such as gravitational wavedetection [19,[23][24][25][26][27], quantum phase estimation [5,[28][29][30][31], quantum magnetometer [32,33], quantum ranging [34][35][36], quantum spectroscopy [37][38][39][40], quantum imaging [41][42][43][44][45][46][47], quantum target-detection [48,49], quantum gyroscope [50,51], distributed quantum sensing [52][53][54], atomic clocksynchronization [55][56][57][58][59][60][61], and even biological measurements [62].…”
Section: Introductionmentioning
confidence: 99%
“…Caves showed that squeezed states of light enable sensitivity beyond the SNL in interferometric measurements 8 . Thirty years later, squeezed light is now an important resource for quantum sensing for a wide range of applications [9][10][11] , with examples ranging from gravitational wave detection 12,13 to plasmonic sensing 11,[14][15][16] to scanning probe microscopies 9,17,18 , magnetometry [19][20][21][22] , Raman spectroscopy [23][24][25] , and spin noise spectroscopy 26,27 . Nonlinear interferometry, in which beamsplitters are replaced with nonlinear amplifiers, has also drawn interest in recent years as an alternative to conventional quantum sensing with squeezed states [28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%
“…OPA is set to a higher gain for broadband parametric homodyne measurement [31,32] and overcoming detection loss [33][34][35], etc. In addition to direct phase sensing, The improved signal-to-noise due to the squeezing was also harnessed for various other applications, such as Raman spectroscopy [36,37] and atomic force microscopy [38]. The SU(1,1) interferometer can operate in multiple regimes, depending on the intensity of the fields: quantum or classical [39], spontaneous or stimulated [40,41], with optical losses shown to degrade the squeezing [42][43][44].…”
mentioning
confidence: 99%